IL-10 Promoter Polymorphism Distribution among HBsAg-Reactive and HBsAg-Nonreactive Blood Donors (Majalah Kedokteran Bandung, 2020)
Hepatitis B surface antigen (HBsAg) serves as a serological marker for Hepatitis B virus (HBV) infection. People with HBV asymptomatic infection might readily donate blood due to the lack of clinical manifestations. Host immunity contributes to susceptibility and progression of infection. A polymorphism in IL-10 gene promoter, rs1800896, might contribute to host immunity. This study was conducted on May 2019 – January 2020 in Faculty of Medicine, University of Riau on  70 blood samples from donors  in the Indonesian Red Cross Pekanbaru. Out of these samples, 35 were reactive for HBsAg and 35 donors were nonreactive. Genotyping of rs1800896 was conducted using Amplification Refractory Mutation System (ARMS-PCR). In total, The distribution of AA (74.3%), AG (24.3%), and GG (1.4%) genotypes revealed in this study seemed to be similar to genotype distribution among East and South-East Asian populations. While no significant difference was observed on age mean and gender distribution, a significant difference was identified in  genotype distribution between HBsAg status (p-value 0.028) with the percentage of AA genotype was higher among HBsAg-nonreactive donors (85.7%) compared to reactive donors (62.9%). More studies should be conducted to characterize HBsAg-reactive blood donors, including the donor characteristics and the viral genotypes. Such studies should contribute to hepatitis B management in Indonesia. Distribusi Polimorfisme Promoter IL-10 pada Donor Darah dengan HBsAg Reaktif dan Nonreaktif di Pekanbaru Hepatitis B surface antigen (HBsAg) merupakan penanda serologis infeksi virus hepatitis B (HBV). Individu dengan infeksi HBV asimptomatik dapat melakukan donasi darah karena tidak adanya gejala klinis. Imunitas inang berkontribusi pada kerentanan dan perkembangan infeksi. Polimorfisme pada promoter gen IL-10, rs1800896, dapat berkontribusi pada imunitas inang. Penelitian dilakukan pada bulan Mei 2019 – Januari 2020 di Fakultas Kedokteran Universitas Riau. Sampel diambil adalah 70 darah donor dari Palang Merah Indonesia Pekanbaru, 35 sampel reaktif HBsAg dan 35 sampel nonreaktif. Genotipe rs1800896 dilihat berdasarkan Amplification Refractory Mutation System (ARMS-PCR). Pada populasi studi ini, distribusi genotipe AA (74.3%), AG (24.3%), dan GG (1.4%) sesuai populasi Asia Timur dan Tenggara. Walaupun tidak terdapat perbedaan pada rerata umur dan distribusi jenis kelamin, penelitian ini menemukan perbedaan signifikan pada distribusi genotipe antar kelompok status HBsAg (p-value 0.028), yaitu persentase genotipe AA lebih tinggi pada kelompok donor dengan HBsAg nonreaktif (85.7%) dibandingkan kelompok reaktif (62.9%). Studi lebih lanjut perlu dilakukan untuk karakterisasi donor darah dengan HBsAg reaktif, termasuk gneotipe donor dan virus. Informasi tersebut diharapkan dapat bermanfaat pada manajemen hepatitis B di Indonesia.
Keywords: blood donor; hepatitis B; HBsAg; IL-10; polymorphism